mTORC2 can associate with ribosomes to promote cotranslational phosphorylation and stability of nascent Akt polypeptide - Oh, Won Jun (Nature Publishing Group, 2010)
The mechanisms that couple translation and protein processing are poorly understood in higher eukaryotes. Although mammalian target of rapamycin (mTOR) complex 1 (mTORC1) controls translation initiation, the function of mTORC2 in protein synthesis remains to be defined. In this study, we find that mTORC2 can colocalize with actively translating ribosomes and can stably interact with rpL23a, a large ribosomal subunit protein present at the tunnel exit. Exclusively during translation of Akt, mTORC2 mediates phosphorylation of the nascent polypeptide at the turn motif (TM) site, Thr450, to avoid cotranslational Akt ubiquitination. Constitutive TM phosphorylation occurs because the TM site is accessible, whereas the hydrophobic motif (Ser473) site is concealed in the ribosomal tunnel. Thus, mTORC2 can function cotranslationally by phosphorylating residues in nascent chains that are critical to attain proper conformation. Our findings reveal that mTOR links protein production with quality control.